Technical paper assessment of school building model under recommended earthquake loading for peninsular Malaysia - Ooi Tze Yang (School of Environmental Engineering, University Malaysia Perlis, 2014)
This paper is written to study how a structural (in this study, a school building is taken as a model) in Malaysia resist against earthquake of which the earthquake magnitude has been scale down according to Malaysian scale. The Malaysian Peak Ground Acceleration (PGA) is 30 gal or 0.03 g. Through Pushover Analysis (POA) which is tested to know its maximum capacity of the building, the maximum capacity of the school building through horizontal axis, Ux is 5.286 mm and through vertical axis, Uz is 0.0630 mm.